(untitled) (REVISTA NODO, 2023)
While throughout its two-thousand-year history the Catholic Church has always used the various arts to convey the message of Jesus Christ to the people, the sacred art of the 20th century is not very well known today. One of the reasons for this absence is the transition from the fascination with avant-garde sacred art that took place in the ecclesiastical world after World War II to the interest in the conservation of the historical heritage in the last decades of the 20th century. This article reviews the careers of six promoters of sacred art in Spain -Josep Torrás, Luis Almarcha, Joan Ferrando Roig, Alfonso Roig, José Manuel de Aguilar and Juan Plazaola- who during the central decades of the 20th century promoted the decorative arts and art dedicated to divine worship, convinced that the mysteries of the Christian faith must be sensitively translated through the genius of artists.